2015
DOI: 10.5935/medicalexpress.2015.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease: a cohort study focusing on treatment response to nutritional counseling

Abstract: BACKGROUND: Nonalcoholic fatty liver disease is the leading cause of liver pathology. The mainstay of management is weight loss. Our aim was to evaluate responses to nutritional counseling in long-term patients with this condition. METHODS: A prospective cohort study with consecutive inclusion of 105 subjects with nonalcoholic fatty liver disease who received individualized low-calories diet counseling (1400 to 1600 kcal/day according to gender) every three months for 24 months. Weight loss of 5% or more was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…A study that followed up a prospective cohort of 105 NAFLD patients every 3 months for 24 months showed that their adherence to dietary advice was poor . It is important to work flexibly with patients on diet .…”
Section: Lifestyle Modification and Nafldmentioning
confidence: 99%
“…A study that followed up a prospective cohort of 105 NAFLD patients every 3 months for 24 months showed that their adherence to dietary advice was poor . It is important to work flexibly with patients on diet .…”
Section: Lifestyle Modification and Nafldmentioning
confidence: 99%
“…Pode ocorrer uma redução do teor dos triacilgliceróis depositados no fígado [14], mediante treinamento físico funcional ou concorrente [15], e a redução do peso corporal [16], principalmente do tecido adiposo abdominal que está diretamente relacionado com a DHGNA [17]. A redução do peso corporal tem melhorado o quadro da DHGNA e da fibrose hepática, principalmente nos pacientes que diminuíram mais de 10% de seu peso corporal [18].…”
unclassified